Mass flow and fate of per- and polyfluoroalkyl substances in a landfill in Uppsala, Sweden - Bonnet, Björn (SLU/Dept. of Aquatic Sciences and Assessment, 2017)
In this study, a landfill has been investigated in terms of the distribution of per- and polyfluoroalkyl substances and the environmental fate. 28 PFASs (13 PFCAs, 4 PFSAs, 3 FOSAs, 2 FOSEs, 3 FOSAAs and 3 FTSAs) have been analysed in 14 leachate, 11 groundwater and 9 sludge samples. Furthermore, 11 samples have been taken in the on-site sewage treatment plant (STP) as well as 12 samples along the receiving water course (total of 57 samples). Sum PFAS concentration in the leachate ranged between 59 ng L−1 and 1500 ng L−1, in groundwater between 8.5 and 1800 ng L−1 and in the sludge between 33 and 438 ng L−1. The composition in the leachate (52%) and the groundwater (60%) was dominated by PFCAs. C3−C7 accounted for 98% sum PFCAs in the leachate and 99% sum PFCAs in the groundwater. Sludge samples ranged from 33 ng L−1 to 440 ng L−1 and were dominated by precursor compounds (FTSAs 37%, PFSAs 33% and PFCAs 7.6% sum PFASs). Long chain PFCAs (C8−C14,C16) showed detection frequencies of 100% (4.8% sum PFASs (C18 included)). PFOS was most abundant in the sludge (30% sum PFASs, 91% sum PFSAs). The STP showed a sum PFASs removal efficiency of 47%, showing highest efficiency for long-chain compounds (88% PFNA, 100% PFDA, 90% PFOS linear and 84% PFOS branched) and precursors (100% for 8:2 FTSA, Me-FOSAA, Et-FOSAA). The total mass flow of PFASs exiting the landfill was estimated with 220 mg g−1. The mass flow in the river showed no long-range effect (30 km) of the landfill concerning the PFASs contamination of surface waters. Conclusively it seems likely that PFASs from the landfill are rather threatening the local groundwater.